Mushroom-derived bioactive components with definite structures in alleviating the pathogenesis of Alzheimer's disease - Xue Jiang; Yu Song; Yu Song; Changshun Lv; Yinghui Li; Xiangru Feng; Hao Zhang; Yujuan Chen; Qingshuang Wang (Frontiers Media S.A., 2024)
Alzheimer's disease (AD) is a complicated neurodegenerative condition with two forms: familial and sporadic. The familial presentation is marked by autosomal dominance, typically occurring early in individuals under 65 years of age, while the sporadic presentation is late-onset, occurring in individuals over the age of 65. The majority of AD cases are characterized by late-onset and sporadic. Despite extensive research conducted over several decades, there is a scarcity of effective therapies and strategies. Considering the lack of a cure for AD, it is essential to explore alternative natural substances with higher efficacy and fewer side effects for AD treatment. Bioactive compounds derived from mushrooms have demonstrated significant potential in AD prevention and treatment by different mechanisms such as targeting amyloid formation, tau, cholinesterase dysfunction, oxidative stress, neuroinflammation, neuronal apoptosis, neurotrophic factors, ER stress, excitotoxicity, and mitochondrial dysfunction. These compounds have garnered considerable interest from the academic community owing to their advantages of multi-channel, multi-target, high safety and low toxicity. This review focuses on the various mechanisms involved in the development and progression of AD, presents the regulatory effects of bioactive components with definite structure from mushroom on AD in recent years, highlights the possible intervention pathways of mushroom bioactive components targeting different mechanisms, and discusses the clinical studies, limitations, and future perspectives of mushroom bioactive components in AD prevention and treatment.